Stress drives myelopoiesis to impair atherosclerosis resolution - Fisher, Edward; Tufanli, Ozlem; Scolaro, Bianca; Civieri, Giovanni; Schlamp, Florencia; Delbare, Sofie; Weinstock, Ada; Cathomas, Flurin; Pena, Stephanie; Berrío, Angélica Torres; Parise, Eric; Chan, Kenny; et al. (Research square, 2025)
Atherosclerotic cardiovascular diseases (ASCVD) remain the leading cause of death globally. Animal and human studies link psychological stress-related disorders to ASCVD. Despite this accumulating evidence linking stress to increased cardiovascular disease (CVD) risk, it remains unclear whether stress impairs the benefits of standard risk-reduction therapies, of which lipid-lowering remains the most common, or whether this increased risk is driven by systemic inflammatory states. We tested the hypothesis that psychological stress limits the benefits of lipid lowering on resolving inflammation in atherosclerotic plaques by combining two established mouse models, namely one in which levels of atherogenic LDL cholesterol (LDL-C) can be lowered after plaques develop, and the other a model of chronic social defeat stress (CSDS). Here we show that mice susceptible to CSDS ("SUS") had attenuated benefits of LDL-C lowering compared to control (CON) or resilient (RES) mice. Moreover, in SUS mice (vs. CON or RES) there was heightened inflammation in the plaque macrophages, with evidence that this was a result of re-programming in the bone marrow (BM) of the precursors of macrophages, namely monocytes. Remarkably, these observations aligned with human imaging studies, in which LDL-C lowering therapy was not as effective in reducing either systemic or arterial inflammation in subjects with higher (vs. lower) neural imaging measures of psychological stress. In summary, the integration of the mouse model and human data provides important mechanistic and clinical insights into the crucial role of chronic stress in ASCVD, highlighting that this common risk factor impairs the anti-atherosclerotic benefits of lipid-lowering medications and may represent an important determinant of residual ASCVD risk.